Life Cycle Assessment untuk Produk Ikan Laut di Kabupaten Gunungkidul - Wahyu Supartono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Life Cycle Assesment (LCA) is one method to assess enviromental aspects and potential effect due to a product or service. This method was conducted by compilation and analysis on input and output data in the system, evaluation on potential effect on enviroment based on the input and output, interpretation of the compilation results and analysis on effects due to the aim of the LCA. This research was intended to find the LCA of sea fishes, ehich were caught and sold in Baron, Drini and Ngrenehan beaches in Gunung Kidul. Other aims were to know the potency of fish products and to evaluate the effects on enviroment if the fishes were processed into the foods. The samples were fresh fish, fried fish and barbequed fish. Results of the research depicted that, catching 1 kg fresh fish was needed 3600 kcal human energy; 7,47 MJ for fuel and produces CO2 0.385 mg, SO2 0.116 mg, NOx 0.0743 mg dan partikel polutan 0.0107 mg. The result of microbiological test showed, value of Total Plate Count lied between 105 to 108. But the results of microbiological tests depicted, that all samples were negative from presence of E.coli, Staphylococcus sp and Salmonella sp (except fresh fish from Baron showed positif contamination of E.coli).